Abstract 13874: N Terminal Pro-Brain Natriuretic Peptide Levels and Benefits of Chronic Total Occlusion Revascularization - Gold, Daniel A; Sandesara, Pratik B; Jain, Vardhmaan; Gold, Matthew E; Vatsa, Nishant; Desai, Shivang; Elhage Hassan, Malika; Yuan, Chenyang; Ko, Yi-An; Liu, Chang; Ejaz, Kiran; Alvi, Zain N; et al. (Circulation (New York, N.Y.), 2023)
Background: The management of chronic total occlusion (CTO) remains a subject of debate, as the mortality benefit from revascularization remains controversial. Whether specific populations gain a survival benefit from CTO revascularization remains unknown. Purpose: In this prospective study of patients with stable coronary artery disease (CAD), we investigated whether patients with CTO have higher adverse event rates and higher N terminal pro-brain natriuretic peptide (NT pro-BNP) levels than patients without CTO. We also investigated whether a higher NT pro-BNP level predicts adverse events in patients with CTO and whether those with elevated NT pro-BNP levels have a survival benefit from revascularization. Methods: In 2,253 patients with significant CAD (>50% coronary luminal stenosis) undergoing cardiac catheterization, all-cause mortality, cardiovascular mortality and the composite of cardiovascular death, myocardial infarction and heart failure hospitalization rates were evaluated. Unadjusted and adjusted Cox proportional and Fine and Gray sub-distribution hazard models were performed to determine the association between NT pro-BNP level and event rates. Results: Patients with CTO had higher incident event rates by > 20% and had higher NT pro-BNP levels than those without CTO (median 230.0 vs. 177.7 pg/mL, p=<0.001). In patients with CTO, every doubling of NT pro-BNP level was associated with > 25% greater risk of adverse events. In patients with elevated NT pro-BNP level (> 125 pg/mL), CTO revascularization was associated with >50% lower adverse event rates than those without CTO revascularization (adjusted cardiovascular death hazard ratio 0.24, 95% confidence interval 0.07 - 0.81). Among patients with low NT pro-BNP level (< 125 pg/mL), event rates were similar in those with and without CTO revascularization. Conclusion: Patients with CTO have higher adverse event rates than those with significant CAD without CTO. NT pro-BNP levels are higher in patients with CTO and higher levels portend a worse prognosis. Moreover, NT pro-BNP levels can help identify individuals who may benefit from CTO revascularization.